POPULISME AGAMA ERA DEMOKRASI DI INDONESIA - Venti Wijayanti (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Abtract Populism as a phenomenon is developing in countries throughout the world. The failure of democracy as a system of government is a major factor in the emergence of populism. Indonesia has only stepped on 20 years of the reign of democracy, religious populism has emerged in fertile fields. The elections of 2016 and 2019 became a phenomenon of the great success of populism in Indonesia. Religious populism can be created because there are three main constituent elements, name- ly: the people, the elite, the public will. Religious populism arises because ideolo- gy can give symbolic legitimacy to control public space. In the face of challenges, the social, global economy comes in the middle, religious populism provides prom- ises of certainty and motivation. The existence of information media that positions everyone can be a source of information about lies so that social polarization appears. Religious populism responds to the political status quo and economic of democratic era in Indonesia. Keywords: Religious populism, Indonesian democracy, Symbolic legitimacy, So- cial polarization